Spatiotemporal Changes in Transcriptome of Odontogenic and Non-odontogenic Regions in the Dental Arch of Mus musculus - Lee, Dong-Joon; Kim, Hyun-Yi; Lee, Seung-Jun; Jung, Han-Sung (Frontiers in Cell and Developmental Biology, 2021)
Over the past 40 years, studies on tooth regeneration have been conducted. These studies comprised two main flows: some focused on epithelial-mesenchymal interaction in the odontogenic region, whereas others focused on creating a supernumerary tooth in the non-odontogenic region. Recently, the scope of the research has moved from conventional gene modification and molecular therapy to genome and transcriptome sequencing analyses. However, these sequencing data have been produced only in the odontogenic region. We provide RNA-Seq data of not only the odontogenic region but also the non-odontogenic region, which loses tooth forming capacity during development and remains a rudiment. Sequencing data were collected from mouse embryos at three different stages of tooth development. These data will expand our understanding of tooth development and will help in designing developmental and regenerative studies from a new perspective.